Participation of Users and Other Stakeholders in Public Construction Projects - Comparison of School Construction Projects in Britain and in Finland - Nevalainen, Suvi-Leena (My University, 2005)
Participation is a major topic both in organizations and in society. Participation and interaction are stressed increasingly in all public processes. Public construction projects are processes in which participation has to be fulfilled very well. That is extremely important for both the process and the results. The nature of a public construction project is complicated and is full of challenges, today’s trends towards increasing interaction in public processes and limited resources put more and more pressure onto project planning. As a part of a research “How to prevent knowledge management failures in public construction projects”, the aim of this study is by using comparative method analyze things to find solutions and develop participation in public construction projects. In the study especially users’ participation during briefing and design is examined; how participation of users and other stakeholders is organized, what forms and tools of participation are there in use and what are they felt to be like. The research problems are approached with mainly three theories; New Public Service –model, Employee Involvement and Organization democracy. As empirical research objects are two school construction projects: a British elementary school and a Finnish primary school. Both of the projects started several years ago and should be finished in 2005. The cases are approximately the same size; there are about 150 children and about fifty personnel in both of the schools. In addition to normal school days, in both of the buildings there are also all kinds of groups for parents and others, day care, and so on going on. These projects are compared by their differences and similarities. The empirical data consists mainly of 15 interviews made using semi-structured interview method in the spring 2004. In addition there are also some documents used as empirical data. The research findings show that there are many forms and tools of participation in use in the projects, and those taking part in the projects are well aware of different kind of forms and tools that could be used. Participation of users in both of the cases was mainly indirect and occurred through their representative(s). Although many of the tools were the same in both of the countries, differences could be found especially in organizing participation, forms of participation and in the way users felt about the projects and their outcomes. In Britain users were much more satisfied with the results than in Finland, which is at least partly because of clearer organizing of the project and better information system.
Keywords: participation; involvement; user; public; construction; fi=Hallintotiede : European Civil Servants - kansainvälisen hallinnon ohjelma|; fi=Kansainvälisen yritystoiminnan koulutusohjelma|